2014
DOI: 10.2174/1381612820666141029101305
|View full text |Cite
|
Sign up to set email alerts
|

Future Perspectives in the Pharmacological Treatment of Atrial Fibrillation and Ventricular Arrhythmias in Heart Failure

Abstract: Heart failure (HF) is a clinical syndrome characterized by significant impairment of cardiac ventricular function. Atrial fibrillation (AF) is the most commonly observed sustained arrhythmia in clinical practice. Both HF and AF are associated with increased morbidity and mortality and their prevalence increases with age. Approximately 50% of patients with moderate HF die due to ventricular fibrillation that leads to sudden cardiac death. Patients with AF exhibit increased mortality due to HF and stroke. HF and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 317 publications
(371 reference statements)
0
2
0
Order By: Relevance
“…Until recently, an oral formulation of vernakalant was being developed in partnership with Merck; however, further development was discontinued in March 2012. It was reported that this decision was based upon “Merck's assessment of the regulatory environment and projected development timeline.” As such, there is still a large unmet need for the development of improved oral antiarrhythmic compounds for AF that are also atrial specific and exhibit few side effects …”
Section: Atrial Fibrillation: a Major Health Concern With Suboptimal mentioning
confidence: 99%
“…Until recently, an oral formulation of vernakalant was being developed in partnership with Merck; however, further development was discontinued in March 2012. It was reported that this decision was based upon “Merck's assessment of the regulatory environment and projected development timeline.” As such, there is still a large unmet need for the development of improved oral antiarrhythmic compounds for AF that are also atrial specific and exhibit few side effects …”
Section: Atrial Fibrillation: a Major Health Concern With Suboptimal mentioning
confidence: 99%
“…Disturbances in ionic homeostasis can lead to electrical disturbances that can manifest as insufficient cardiac output/relaxation and cardiac arrhythmias, especially in HF [81][82][83][84]. Targeting the underlying ionic imbalances associated with HF, therefore, represents an attractive therapeutic strategy [85][86][87][88].…”
Section: Ion Handling In Heart Failure Sudden Cardiac Death and Arrhy...mentioning
confidence: 99%